2007
DOI: 10.4028/www.scientific.net/ssp.130.281
|View full text |Cite
|
Sign up to set email alerts
|

Lattice and Peak Profile Parameters in GIXD Technique

Abstract: Grazing incident X-ray diffraction technique was applied to determine the influence of incident beam angle (α angle) on structural parameters as well as peak profile. X-ray diffraction patterns were registered in asymmetrical geometry, in which a parallel beam was formed by Soller and divergence slits. Lowering of the α angle results in accuracy decrease of lattice parameters as well as in significant broadening of a half-width of X-ray diffraction line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…However, fixation of an angle (α angle) between the primary X-ray beam and sample surface leads to asymmetry in focusing of rays in GIXD technique. Accurate measurements carried out, using LaB 6 and Al 2 O 3 standard reference materials, have shown that parameters of diffraction line such as: position, intensity, half-width and peak shape differ from those obtained in classical Bragg-Brentano (B-B) geometry [5]. However, the crystallite size of these standards was in micro-scale.…”
Section: Introductionmentioning
confidence: 97%
“…However, fixation of an angle (α angle) between the primary X-ray beam and sample surface leads to asymmetry in focusing of rays in GIXD technique. Accurate measurements carried out, using LaB 6 and Al 2 O 3 standard reference materials, have shown that parameters of diffraction line such as: position, intensity, half-width and peak shape differ from those obtained in classical Bragg-Brentano (B-B) geometry [5]. However, the crystallite size of these standards was in micro-scale.…”
Section: Introductionmentioning
confidence: 97%
“…Figure 4 shows the È-scan results of {440} reflections, where one can see that there are three To gain insight into the heterostructures in more detail, we further analyzed their in-plane structures along the Si( " 1 110) plane using the GIXD with synchrotron radiation of 10 keV. 13,14) The GIXD technique is very powerful in investigating the in-plane structures of thin films due to its superior surface sensitivity. The synchrotron radiation with high energy is selected throughout the measurement because of the insufficient energy provided by the usual X-ray.…”
Section: Resultsmentioning
confidence: 99%
“…The grazing incidence X-ray diffraction (GIXD) patterns were recorded over a 2θ range from 10 • to 80 • with a 0.05 • step size for the incident angle (α = 0.25 • ). 21,22 Electrochemical analysis.-The corrosion resistance of the titanium alloys samples was investigated using Ringer's solution, which is composed of 8.6 g dm −3 NaCl, 0.3 g dm −3 KCl, and 0.48 g dm −3 CaCl 2 • 6H 2 O (Baxter, USA). The apparatus included a standard twochamber electrolysis cell with three electrodes: a working electrode, a platinum auxiliary electrode and a Haber-Luggin capillary with a reference electrode (saturated calomel electrode -SCE).…”
Section: Methodsmentioning
confidence: 99%